Social Networks, Promotions, and the Glass-Ceiling Effect - Anna Zaharieva; Michael Neugart (ZBW - Leibniz Information Centre for Economics, 2020)
Empirical studies show that women are under-represented in highly paid top management positions of firms (glass-ceiling effect) which could be a cause of the gender wage gap. In order to study women's career paths, we develop a search and matching model where job ladders consist of three hierarchical levels and workers can progress in the career by means of internal promotions and job-to-job mobility. Both, formal applications and referral hiring via endogenous social networks, can be used for external moves between firms. We show that when female workers are the minority in the occupation and social link formation is gender-biased (homophily) there are too few female contacts in the social networks of their male colleagues. This disadvantage implies that female workers are referred less often and, thereby, become under-represented in top level management positions of firms. Our results suggest that endogenously forming homophilous social networks when female workers are the minority can explain a substantial part of the empirically observable total wage gap stemming from the glass-ceiling effect. In addition, we demonstrate that the effects on an unequal gender-representation are amplified by stronger clustering of social networks, and gender-biased promotion times. Furthermore, deeper hierarchical firm structures amplify the network-driven gender inequality but mitigate inequality arising from direct discrimination in internal promotions.
Keywords: D21; D85; J31; J63; J71; 330; glass-ceiling effect; networks; discrimination; theory of the firm; promotions; search-and-matching labor market